Penerapan Media Puzzle untuk Meningkatkan Hasil Belajar Musik di Kelas VIII-G SMPN 10 Malang - Dewi, Vera Indriani; D.P, Endang Wara Suprihatin (Innovative: Journal Of Social Science Research, 2025)
This study aims to describe the effectiveness of puzzle media to improve music learning outcomes in class VIII-G students of SMPN 10 Malang City. Applying pre-experiment method with pre-test post-test design in quantitative approach. The research subjects were students of class VIII-G totaling 30 students. The population in this study were all students in grade VIII at SMP Negeri 10 Malang. Data collection used documentation of students' learning outcomes. The t-test test was applied to analyze the research data, with the independent variable, namely puzzle media and music learning outcomes as the dependent variable. Based on the results of the learner knowledge test, the following data were obtained; Significant increase in learning outcomes after intervention (p < 0.001, N-Gain = 0.518). This increase is due to the puzzle media in increasing learner involvement, facilitating concept visualization, and training problem solving skills. The results suggest that puzzle media can be an effective alternative in improving music learning outcomes.